Sensitivity to cocaine in adult mice is due to interplay between genetic makeup, early environment and later experience. (October 2017) - Di Segni, Matteo; Andolina, Diego; Coassin, Alessandra; Accoto, Alessandra; Luchetti, Alessandra; Pascucci, Tiziana; Luzi, Carla; Lizzi, Anna Rita; D'Amato, Francesca R.; Ventura, Rossella
Abstract: Although early aversive postnatal events are known to increase the risk to develop psychiatric disorders later in life, rarely they determine alone the nature and outcome of the psychopathology, indicating that interaction with genetic factors is crucial for expression of psychopathologies in adulthood. Moreover, it has been suggested that early life experiences could have negative consequences or confer adaptive value in different individuals. Here we suggest that resilience or vulnerability to adult cocaine sensitivity depends on a "triple interaction" between genetic makeup x early environment x later experience. We have recently showed that Repeated Cross Fostering (RCF; RCF pups were fostered by four adoptive mothers from postnatal day 1 to postnatal day 4. Pups were left with the last adoptive mother until weaning) experienced by pups affected the response to a negative experience in adulthood in opposite direction in two genotypes leading DBA2/J, but not C57BL/6J mice, toward an "anhedonia-like" phenotype. Here we investigate whether exposure to a rewarding stimulus, instead of a negative one, in adulthood induces an opposite behavioral outcome. To test this hypothesis, we investigated the long-lasting effects of RCF on cocaine sensitivity in C57 and DBA female mice by evaluating conditioned place preference induced by different cocaine doses and catecholamine prefrontal-accumbal response to cocaine using a "dual probe" in vivo microdialysis procedure. Moreover, cocaine-induced c-Fos activity was assessed in different brain regions involved in processing of rewarding stimuli. Finally, cocaine-induced spine changes were evaluated in the prefrontal-accumbal system. RCF experience strongly affected the behavioral, neurochemical and morphological responses to cocaine in adulthood in opposite direction in the two genotypes increasing and reducing, respectively, the sensitivity to cocaine in C57 and DBA mice. Highlights: Genetic makeup interacts with early experience and later experiences in adulthood. Early environment affects cocaine response in adulthood depending on the genotype. Early environment modifies behavioral, neurochemical and morphological response to cocaine. Early environment increases cocaine susceptibility in C57BL6/J mice.